1993
DOI: 10.1007/bf01976212
|View full text |Cite
|
Sign up to set email alerts
|

Differential inhibition of human secretory and cytosolic phospholipase A2

Abstract: The roles and relative contributions of secretory and cytosolic phospholipases A2 in physiology and pathology are not precisely known. In a search for differential inhibitors of these enzymes, which could serve as tools to clarify this issue, we evaluated the potencies of reference compounds and three series of new compounds, viz. substrate analogues, 1,2-amino alcohols and enolized beta-tricarbonyl derivatives, as inhibitors of secretory phospholipase A2 from human polymorphonuclear leukocytes (sPLA2) and of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Crystallographic experiments on porcine pancreatic type I PLA 2 showed that a free ␣-amino group is an essential requirement for enzyme activity (15,17,32,33). In type II PLA 2 from C. atrox, strong hydrogen bonding occurs between the NH 2 -terminal ␣-amino group and the side chain of residue 4 with the backbone carbonyls and amides of residues 71 and 73 (25).…”
Section: Discussionmentioning
confidence: 99%
“…Crystallographic experiments on porcine pancreatic type I PLA 2 showed that a free ␣-amino group is an essential requirement for enzyme activity (15,17,32,33). In type II PLA 2 from C. atrox, strong hydrogen bonding occurs between the NH 2 -terminal ␣-amino group and the side chain of residue 4 with the backbone carbonyls and amides of residues 71 and 73 (25).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that several inhibitors of cPLA 2 have been discovered, e.g. arachidonyl trifluoromethyl ketone (AACOCF 3 ) ( 1 ) and (S) - N -hexadecylpyrrolidine-2-carboxamide (Wy-48,489) ( 2 ), no compound has been reported to be undergoing clinical development. Moreover, only a few structure−activity relationship investigations relating to those enzyme inhibitors have been published to date.…”
Section: Introductionmentioning
confidence: 99%
“…Märki et al [131] reported an IC50 of 15 µM for Wy-48489 against h-cPLA2 isolated from the U937 cell line.…”
Section: Pla2 Inhibitors From Wyeth-ayerstmentioning
confidence: 99%
“…Wy-49422 (oxiranecarboxylic acid, 2-[5-(4-chlorophenyl)pentyl]-ethylester) was also described as an sPLA2 inhibitor [131], and the compound depressed human platelet and synovial sPLA2s with IC50 values of 18 and 36 µM, respectively. Wy-49422 and Wy-48489 were derived from two different structural classes, but both agents were anti-inflammatory in vivo (phorbol ester-induced mouse ear oedema, carrageenan-induced rat paw oedema).…”
Section: Pla2 Inhibitors From Wyeth-ayerstmentioning
confidence: 99%